Enciclopedismo em Livros de Artista: um manual de construção da Enciclopédia Visual - Amir Brito Cadôr (2012)
The study of encyclopedism in artists books is presented in the form of an encyclopedia, which is also a construction manual for a Visual Encyclopedia. Using description as the working methodology, this work analyzes artists books that belong to the special collection of EBA / UFMG. The poetics of the archive, the collection and the inventoryare studied. The art of memory, montage and allegory are themes of some chapters of the thesis. Other chapters highlight the editorial paratexts and material aspects of the works. The thesis also discusses about production and transmission of knowledge through images, as well as its graphical representations.